2020
DOI: 10.1007/s00112-020-01076-7
|View full text |Cite
|
Sign up to set email alerts
|

Alice im digitalen Wunderland: pädiatrische Lehre in der COVID-19-Pandemie

Abstract: ZusammenfassungDie Umstellung der pädiatrischen Lehre im Medizinstudium von Präsenzveranstaltungen auf digitale Formate war und ist für Lehrende und Studierende eine besondere Herausforderung. Basierend auf einer Umfrage unter pädiatrischen Universitätskliniken fasst die AG Lehre der DGKJ im folgenden Beitrag bisherige Erfahrungen zur digitalen Lehre im Sommersemester 2020 zusammen. Die Umfrageteilnehmer von 17 pädiatrischen Universkliniken berichteten über ein umfangreiches Spektrum oft kurzfristig entwickelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
3
0
3
Order By: Relevance
“…This coincides with the results of other studies. For example, Häusler et al were able to show that radiology lectures and seminars can be implemented particularly effectively using a digital format 12 . However, as in other studies, Häusler et al came to the conclusion that digital lectures and seminars are less suitable for teaching practical skills due to the low level of interactivity 13 14 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This coincides with the results of other studies. For example, Häusler et al were able to show that radiology lectures and seminars can be implemented particularly effectively using a digital format 12 . However, as in other studies, Häusler et al came to the conclusion that digital lectures and seminars are less suitable for teaching practical skills due to the low level of interactivity 13 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, working on cases together in learning groups could actually increase discipline-specific interaction compared to traditional in-person learning. Häusler et al concluded in their study that a digital teaching unit should be thematically strictly limited to the learning objectives 12 . Our results showed significant subjective learning gains in all topic-specific course modules.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations